Experimental Algorithms 6th International Workshop, WEA 2007, Rome, Italy, June 6-8, 2007, Proceedings - Demetrescu, Camil.; Demetrescu, Camil. (Theoretical Computer Science and General Issues, 2007)
This book constitutes the refereed proceedings of the 6th International Workshop on Experimental and Efficient Algorithms, WEA 2007, held in Rome, Italy, in June 2007. The 30 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 121 submissions. Fostering and disseminating high quality research results focused on the experimental analysis of algorithms the papers are devoted to the design, analysis, implementation, experimental evaluation, and engineering of efficient algorithms. Among the application areas addressed are most fields applying advanced algorithmic techniques, such as combinatorial optimization, approximation, graph theory, discrete mathematics, data mining, simulation, cryptography and security, scheduling, searching, sorting, string matching, coding, networking, etc.